2022
DOI: 10.1155/2022/6082179
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Acupuncture Treatment for Oral Ulcer

Abstract: Background. Oral ulcer (OU) is a common oral mucosal disease manifested with obvious pain. In some studies, the efficacy of acupuncture in OU has been confirmed, but systematic reviews and meta-analyses for them are lacking. Our aim is to evaluate the efficacy of acupuncture in the treatment of OU. Methods. We searched the literature from eight databases from their inception to December 2021. We included randomized controlled trials of acupuncture for the treatment of oral ulcer. The meta-analysis was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 23 Further screening more effective medications with lower side effects to promote wound healing by reducing inflammation, relief of pain and reduction of oral ulcer duration is still a major challenge for the treatment of oral ulcers. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 23 Further screening more effective medications with lower side effects to promote wound healing by reducing inflammation, relief of pain and reduction of oral ulcer duration is still a major challenge for the treatment of oral ulcers. 24 …”
Section: Discussionmentioning
confidence: 99%
“…As a mild self-limiting disease, OU has a great effect on personal daily life due to recurrent and chronic nature. [ 19 ] Most studies have shown that the recurrence of OU is related to immune inflammation. There is increased cytokines release such as IL-6 and TNF-α in the peripheral blood cells of patients having recurrent ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent oral ulcer (ROU), also known as a recurrent aphthous ulcer, is a common oral mucosal disease. 1 It is commonly found on the margin of the tongue, lips and cheeks, with a prevalence rate of up to 20%. 2 It is characterized by periodic recurrence and generally has a long initial attack period and a short recurrent attack period.…”
Section: Introductionmentioning
confidence: 99%